Reduced Turn-On Voltage for npn Graded-Base AlGaN/GaN Heterojunction Bipolar Transistors by Thermal Treatment - Shih-Wei Tan; Shih-Wen Lai (Advances in Materials Science and Engineering)
A thermal treatment was employed to improve the DC performances of npn graded-base AlGaN/GaN heterojunction bipolar transistors (HBTs). Such HBTs without the thermal treatment exhibit a higher turn-on voltage of 6.45 V, a lower current gain of 0.84, and a lower collector current of 3.18 × 10−4 mA at of 4.5 V. The HBTs are examined by thermal treatment with rapid thermal process (RTP) annealing at various times and various temperatures. Experimental results reveal that the HBTs with the thermal treatment exhibit a lowest turn-on voltage of 3.90 V, a highest current gain of 9.55, and highest collector current of 112.2 mA at of 4.5 V. The thermal treatment brings forth the most remarkable improvements for the HBTs when the base parasitical Schottky diodes are modified.